2022
DOI: 10.3390/vaccines10091477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prior Infection with SARS-CoV-2 on B Cell Receptor Repertoire Response during Vaccination

Abstract: Understanding the B cell response to SARS-CoV-2 vaccines is a high priority. High-throughput sequencing of the B cell receptor (BCR) repertoire allows for dynamic characterization of B cell response. Here, we sequenced the BCR repertoire of individuals vaccinated by the Pfizer SARS-CoV-2 mRNA vaccine. We compared BCR repertoires of individuals with previous COVID-19 infection (seropositive) to individuals without previous infection (seronegative). We discovered that vaccine-induced expanded IgG clonotypes had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Those who were previously infected with SARS-CoV-2 in all age cohorts had higher levels of antibodies and responded more actively to the administration of booster doses of Sputnik V. This may be due to the different clonotypes of B cells formed during revaccination and SARS-CoV-2 infection [ 23 ], which may lead to the formation of more effective hybrid immunity against COVID-19 [ 24 ]. Age cohorts showed that individuals younger than 60 years had significantly lower levels of antibodies, regardless of previous COVID-19 contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Those who were previously infected with SARS-CoV-2 in all age cohorts had higher levels of antibodies and responded more actively to the administration of booster doses of Sputnik V. This may be due to the different clonotypes of B cells formed during revaccination and SARS-CoV-2 infection [ 23 ], which may lead to the formation of more effective hybrid immunity against COVID-19 [ 24 ]. Age cohorts showed that individuals younger than 60 years had significantly lower levels of antibodies, regardless of previous COVID-19 contraction.…”
Section: Discussionmentioning
confidence: 99%
“…50 The BCR-CDR3 Shannon index was higher in the seropositive group compared to the seronegative group post Pfizer-mRNA vaccination. 51…”
Section: Bcr-cdr3 Monitoring and Analysis Methods After Sars-cov-infe...mentioning
confidence: 99%
“…BCR‐CDR3 diversity increased at 28 days after CoronaVac inactivated vaccination 50 . The BCR‐CDR3 Shannon index was higher in the seropositive group compared to the seronegative group post Pfizer‐mRNA vaccination 51 …”
Section: Bcr‐cdr3 Features Changes and Significance In Sars‐cov‐2 Inf...mentioning
confidence: 95%
See 2 more Smart Citations